Psoriasis and quality of life - Bender, Andressa Galleas; Freitas, Lucelia Maria de; Borges, Beatriz Essenfelder (Seven Editora, 2023)
Introduction: Psoriasis is a chronic skin disease characterized by inflammation, which is not contagious. The treatment of this condition is personalized, considering the patient's clinical condition, the history of the disease, and the severity of the injuries. Psoriasis stands out for having significant psychosocial consequences, due to visible lesions on the skin, resulting in significant restrictions in daily and social activities, thus compromising Quality of Life (QoL). Objective: This article seeks to understand psoriasis and describe the main characteristics that affect the QoL of patients, addressing the advances in the field of health related to this condition. Methodology: The study consists of an integrative literature review, delimited in the publication period of the last 10 years. For the selection of publications, inclusion criteria were applied, where it was decided to use a form for data collection, covering information related to the identification of the study, such as year of publication, type of study, study objective, sample used and research results. Discussion:  According to the data analysis, it was possible to understand the main etiopathogenic aspects, diagnostic methods, and therapeutic approaches of psoriasis, where we have the dimension of the damage caused to the patient's QoL. From this, the disease presents itself as a skin condition triggered by multiple external factors that activate the individual's immune system. Regarding the etiology, it was clear that it involves genetic and environmental aspects. In addition, the treatment should be carried out in a multidisciplinary way. Conclusion: It is essential to highlight that the patient's QoL is directly related to the patient's health status and disease severity. QoL is an important indicator to guide the treatment and prognosis and management of the disease. Thus, there is an improvement in the QoL of patients after the beginning of drug treatment since it improves the visual aspect of the disease. DOI:https://doi.org/10.56238/interdiinovationscrese-032